1980
DOI: 10.1115/1.3251576
|View full text |Cite
|
Sign up to set email alerts
|

Performance Characteristics of Two-Lobe Hydrodynamic Journal Bearings

Abstract: The performance characteristics of noncircular bearings are known to be superior to those of the circular bearings. The two lobe bearings are finding increasing application in high speed turbomachinery. Using a variational solution, detailed design data have been computed for two-lobe bearings in this paper. The data include Sommerfeld number, equilibrium locus, fluid film stiffness and damping coefficients, end-flow, friction parameter, and temperature rise parameter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…Equation (6) gives the steady-state pressure distribution and (7) and (8) give the dynamic pressure distribution in each individual lobe.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Equation (6) gives the steady-state pressure distribution and (7) and (8) give the dynamic pressure distribution in each individual lobe.…”
Section: Theorymentioning
confidence: 99%
“…Kumar et al [7] had done the detail study and analysis of two-lobe pressure bearing and shown the superiority of these bearings over conventional circular bearing. Static and dynamic characteristics of orthogonally displaced pressure dam bearing had been studied by Mehta [8].…”
Section: Introductionmentioning
confidence: 99%
“…The different sections includes two-lobed, three-lobed and four-lobed bearings, micropolar lubrication, lubrication with non-Newtonian lubricants, porous bearings and comparative study of different bearing configurations. Kumar et al (1980) computed a design data using a variational solution which included Sommerfeld number, equilibrium locus, damping coefficient, fluid film stiffness, temperature rise parameter and end flow friction parameter.…”
Section: Review Of Non-circular Bearingsmentioning
confidence: 99%
“…Therefore, researchers showed interest to examine the noncircular (lobed) bearing. The analysis of lobed bearing was given by [4][5][6][7]. These researchers analyzed the performances of such bearings and found that lobed bearings were much better in stability, which was the main problem of high speed rotating machineries.…”
Section: Introductionmentioning
confidence: 99%